2004
DOI: 10.1590/s0103-84782004000500042
|View full text |Cite
|
Sign up to set email alerts
|

Técnica para o estudo da anatomia da epiderme foliar de batata

Abstract: RESUMO Embora a batata (SolanumA batata cultivada (Solanum tuberosum) pertence à família Solanaceae. A batata é considerada a quarta cultura mais importante do mundo, sendo superada apenas pelo trigo, arroz e milho (ANONYMOUS, 1998). Embora seja uma espécie economicamente importante, são poucas as informações disponíveis na literatura referentes às descrições da anatomia foliar, no que diz respeito às características da epiderme, como espessura de cutícula, número, forma e localização dos estômatos e pêlos das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 4 publications
2
28
0
13
Order By: Relevance
“…The number of glandular and non-glandular trichomes on these three apical leafl ets was also registered in order to correlate whitefl y oviposition with trichome density. Trichome numbers were determined using the epidermal fi ngerprint technique (Segatto et al 2004), and trichome density was calculated according to McAuslane (1996).…”
Section: Methodsmentioning
confidence: 99%
“…The number of glandular and non-glandular trichomes on these three apical leafl ets was also registered in order to correlate whitefl y oviposition with trichome density. Trichome numbers were determined using the epidermal fi ngerprint technique (Segatto et al 2004), and trichome density was calculated according to McAuslane (1996).…”
Section: Methodsmentioning
confidence: 99%
“…Despite wide use, anatomical studies apply laborious techniques (Macedo, 1997) that make work hard and long time-consuming. Segatto et al (2004) demonstrated a study of leaf epidermis anatomy in potato clones (Solanum tuberosum L.) by an alternative technique, the printing out of leaf epidermis with cianoacrilate ester universal instantaneous adhesive. The aim of this work was to identify some Lauraceae tree species from remnants of Seasonal Forests at Serra Geral formation, Rio Grande do Sul state, applying the epidermical printing technique with cianocrilate ester as an alternative anatomic tool.…”
Section: Introductionmentioning
confidence: 99%
“…Para ilustração da superfície epidérmica, foram retiradas amostras das folhas e realizadas impressões paradérmicas do material (Segatto et al, 2004).…”
Section: Methodsunclassified